Back Cover: Copper‐Catalyzed Alkoxycarbonylation of Alkanes with Alcohols (ChemSusChem 7/2017). Issue 7 (4th April 2017) - Li, Yahui; Wang, Changsheng; Zhu, Fengxiang; Wang, Zechao; Dixneuf, Pierre H.; Wu, Xiao‐Feng
Abstract : The Back Cover picture shows and ancient ding, which has been used as food container in China since the Chalcolithic period. It is made from copper, and later on it has become a symbol of power. The term "inquiring of the ding" (Chinese:, pinyin: wèn diǎng) is often used interchangeably with the quest for power. In our work, we succeeded in the copper‐catalyzed alkoxycarbonylation of alkanes. It is a challenging transformation, and succeeding in this reaction is a kind of "wen ding". Esters were produced from the copper‐made ding, representing the good smell of food and also delivering best wishes (A harvest year!).